Growth Pattern of Grouper Sunu (Plectropomus leopardus) At the Kurau Beach Fishing Port Central Bangka Regency - Fitrianisa, Aniz; Nurhayati, Nurhayati; Lisna, Lisna (Jurnal Perikanan dan Kelautan, 2020)
Sunu grouper fish belongs to the Seranidae family whose pattern of reproduction is anti hermaphrodite protogyny, which is the gonad as an organ that changes the transition from the female to male phase. The aims of this research is to study the growth pattern of Sunu grouper fish and find out the total of female Sunu grouper or male Sunu grouper that caught a lot. This research was conducted at the Port of Kurau Coastal Fisheries, Central Bangka Regency, Bangka Belitung Province from February to March 2020 using a survey method. The results showed that the catch of tiger grouper fish reached 399,94 kg, consist of 283,44 kg or 581 female fish species and 116,50 kg or 69 fish according to male sex. The total number of fish caught during the study was 650 fish with the growth pattern is allometric positif. The results also showed a coefficient of determination (R2) of female groupers 0.938 and a value of determination (R2) of 0.701 in male groupers. Based on the results of research that has been done can conclude the growth pattern of female Sunu grouper is allometric positif with value 3,09 and the growth pattern of male Sunu grouper is allometric positif with value 3,87. The total of Sunu grouper fish catch along research is about 650 fish consist of 581 female grouper fish and 69 male grouper fish.